Three Periods of Jadid Storytelling (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines Jadid storytelling which emerged in Turkestanat the beginning of the 20th century,its periodization, first stories and their uniqueness. The development of Uzbek Jadid storytelling is analyzed in three periods: formation (1905–1917), development (1917–1925), and decline (1925–1929). The stories of enlightenment figures such as Makhmudkhoja Bekhbudi, Abdulla Qodiriy, Chulpon, Munavvarqori Abdurashidkhanov, Said Ahroriy, and Elbek are examined in detail.